Effect of calcium fertilization on silver vase bromeliad (Aechmea fasciata) - Milioni, Claus Baumgarten; Kawakubo, Lucas Hiroshi [UNESP]; Kanashiro, Renato Jocys; Santos, Vanessa Reboucas dos; Kanashiro, Shoey; Tavares, Armando Reis (Soc Brasileira Floricultura & Plantas Ornamentais, 2019)
The present study aimed to evaluate the effect of different concentrations of calcium on growth and development of silver vase bromeliad (Aechmea fasciata). Plants were fertilized three times a week with nutrient solutions formulated with HA solution (Hoagland and Arnon, 1950) modified with 0.25, 2.5, 5, 7.5, 10.0 or 12.5 mM Ca applied into the tank. After 90 days of experimentation, biometric and biomass measurements of root and shoot systems, and chemical analysis of leaves were assessed. The results showed that the concentration of 12.5 mM Ca in nutrient solution is recommended for silver vase bromeliad fertilization.
Keywords: Bromeliaceae; plant nutrition; fertilization; calcium nitrate